The impact of the use of correction techniques in the self-esteem and academic oral performance of the students of basic intensive English of the Bachelor of Arts in modern Languages with Specialization in French and English, semester I-2018 - Martínez Galdámez, Katherine Marjorie; Orellana Guardado, Xitlaly Margarita; Ruíz Rodríguez, Carlos Alfredo (2024)
This research work was done with the purpose of demonstrating the impact that error correction techniques can have in the oral performance of students. Throughout the years, students receive feedback or they are corrected by their professors during the class time; however, professors do not know if they are giving the appropriate feedback or how they are affecting the students‟ self-esteem when they get corrected orally, which can lead the students, if they are inappropriately corrected, to either decrease their level of proficiency in the subject or, in the worst case scenario, to drop out their studies. In the pursuit of guaranteeing the quality in the professor-student interaction while developing oral activities in the future generations, this research is focused on finding out how the correction techniques are applied and their effects on students after they have participated. The mixed-method design is used by administering interviews for professors, questionnaires for students, observation guides as well as the Rosenberg scale to measure the student´s self-esteem level before and after they have been corrected in any oral activities in class. The effects that come along with the correction techniques are demonstrated through the data presented in this investigation. Certainly, there is an emotional response when a subject is corrected by someone else; that emotional response can be external, which is noticeable by looking at the gestures that students can make when they are corrected, or it could be an internal response that might be noticed when they are asked to participate again and they do not want to do it; however, in both cases, it is needed to talk with the subjects so they can externalize their opinions.